Adolescent utilization of sexual and reproductive health services in Gamo Zone, Southern Ethiopia. Insights from multilevel and latent class analysis - Sidamo, Negussie Boti; Abebe Kerbo, Amene; Gidebo, Kassa Daka; Wado, Yohannes Dibaba (Frontiers in Reproductive Health, 2024)
Introduction: Adolescents face unique challenges related to their sexual and reproductive health (SRH), with access to timely services being critical for positive outcomes. However, SRH service utilization among adolescents remains low. This study aimed to identify factors influencing SRH service use among adolescents in Gamo Zone, Ethiopia. Methods: A community-based cross-sectional study involved 1172 adolescents selected through stratified sampling. Structured face-to-face interviews were employed for data collection. Multilevel mixed logistic regression was fitted to identify factors and latent class analysis was conducted to understand population heterogeneity. Results: The findings of this study reveal that 198 (16.89%) adolescents (95% CI: 14.8%-19.2%) utilized SRH services within the past 12 months. Factors significantly associated with SRH service utilization included good knowledge about SRH rights (AOR = 4.65; 95% CI: 2.68, 8.07), belonging to one-parent families (AOR = 4.13; 95% CI: 2.39, 7.12), engaging in parental discussions regarding SRH issues (AOR = 3.17; 95% CI: 1.89, 5.29), high family support (AOR = 1.96; 95% CI: 1.09, 3.51), and enrolling in school (AOR = 0.19; 95% CI: 0.11, 0.33). Additionally, access to social media was associated with increased SRH service utilization among adolescents (AOR = 1.98; 95% CI: 1.25, 3.15). The latent class analysis identified four groups: rural school-enrolled adolescents living with parents, urban school-enrolled adolescents with both parents, urban disadvantaged female adolescents, and early adolescents with limited social media access. Conclusions: In conclusion, our study sheds light on the utilization of SRH services among adolescents, revealing that 16.89% of the participants accessed these services within the past year. Significant factors associated with SRH service utilization included good knowledge about SRH rights, belonging to one-parent families, engaging in parental discussions regarding SRH issues, high family support, and school enrollment. Interestingly, access to social media was also linked to increased utilization of SRH services among adolescents. Furthermore, our latent class analysis identified four distinct classes of adolescents based on socio-demographic indicators, highlighting the heterogeneity within this population. These findings underscore the importance of tailored interventions and targeted approaches to address the diverse needs of adolescents in accessing and utilizing SRH services.